Feed additives for methane mitigation: Assessment of feed additives as a strategy to mitigate enteric methane from ruminants. Accounting; How to quantify the mitigating potential of using antimethanogenic feed additives - del Prado, Agustín; Vibart, Ronaldo; Bilotto, Franco; Faverin, Claudia; García, Florencia; Henrique, Fábio; Leite, Fernanda Figueiredo Granja Dorilêo; Mazzetto, Andre; Ridoutt, Bradley; Yáñez Ruiz, David; Bannink, André (Elsevier, 2025)
Recent advances in our understanding of methanogenesis have led to the development of antimethanogenic feed additives (AMFA) that can reduce enteric methane (CH4) emissions to varying extents, via direct targeting of methanogens, alternative electron acceptors, or altering the rumen environment. Here we examine current and new approaches used for the accounting (i.e., quantification) of enteric CH4 abatement by the use of AMFA in the livestock sector from the individual animal to the global scale. Along with this process, recommendations are provided on how to account for the mitigation potential at the animal level, as well as in farm-scale models, emissions trading schemes, life cycle assessment, and carbon (C) footprinting tools, and in regional and national inventories. In addition, an assessment of uncertainties and potential trade-offs and off-setting with the use of AMFA (i.e., efficacy vs. effectiveness, upstream and downstream emissions) is provided. The accounting of on-farm enteric CH4 emissions and benefits from the use of AMFA starts with the ruminant animal (with estimates obtained from a range of approaches, from simple empirical emission factors or equations to complex process-based models) and goes all the way to national and supranational accounting. The choice of methodologies and levels of complexity to account for mitigation of enteric CH4 (or total GHG) emissions in livestock systems must be tailored to the scale of analysis aimed, the availability of input data to represent contextualized conditions, and the accounting objectives (e.g., academic exercise vs. producer's GHG certification vs. national GHG inventory). The accounting of enteric CH4 mitigating effects needs to consider the AMFA delivery methods and synergies and trade-offs of GHG emissions at levels before and beyond (upstream and downstream) the animal to fully assess the impact of AMFA use. At large, the accounting of methane abatement by feed additives remains to be fully assessed beyond experimental results (efficacy) to address pragmatism (effectiveness), potential for adoption, and societal acceptance.